Potential of cypermethrin or diazinon and their combined action with piperonyl butoxide (PBO) against Periplaneta americana L - Rahman, ASM Shafiqur; Akter, MY (University Journal of Zoology, Rajshahi University, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> No Abstract Key words: Periplaneta americana, diazinon, cypermethrin, LD50, synergist doi:10.3329/ujzru.v27i0.1966 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 101-102